2012
DOI: 10.1177/0021998312452763
|View full text |Cite
|
Sign up to set email alerts
|

Study on the possibility of increasing the maximum allowable stresses in fibre-reinforced plastics

Abstract: This article presents the results of a study aimed at investigating the possibility of increasing the maximum allowable stresses in fibre-reinforced plastics compared to current practice. The study consisted of a comparison between the maximum allowable stresses of a group of cross-ply laminates, determined by deterministic analyses with safety and model factors as stated in design rules, and their probabilistic responses estimated with a fracture mechanics based model that accounted for material degradation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…There is a need to clearly define failure of composites. From comparative studies between deterministic and probabilistic analyses of cross-ply laminates under tension Sánchez-Heres et al [10] concluded that an increased understanding is required regarding the effects of progressive matrix cracking in order to reach a safer structure.…”
Section: Fig 1 Damage Developmentmentioning
confidence: 99%
“…There is a need to clearly define failure of composites. From comparative studies between deterministic and probabilistic analyses of cross-ply laminates under tension Sánchez-Heres et al [10] concluded that an increased understanding is required regarding the effects of progressive matrix cracking in order to reach a safer structure.…”
Section: Fig 1 Damage Developmentmentioning
confidence: 99%
“…There is a need to clearly define failure of composites. From studies with crossply laminates, Sa´nchez-Heres et al 9 found out that an increased understanding is required regarding the effects of matrix cracks, and therefore the maximum allowable crack density, in order to reach a safer structure.…”
Section: Introductionmentioning
confidence: 99%